(untitled) (Teaching and Learning Inquiry, 2023)
The adoption of digital technologies in higher education offers new opportunities for student learning but also adds complexity to course design and development processes. Although practice varies across institutions and nations, a common response is that teams of people are now involved in the development and creation of blended and online courses. Members of such teams typically include instructional designers, academics, learning designers and technologists, and production teams, and courses are developed over time, often across separate locations and organisations. These factors are creating a need for tools that support the sharing of design information in distributed course design teams. This paper introduces such a course design tool, EdVee, which supports pedagogical innovation through the sharing and visualisation of constructive alignment of learning outcomes, content, learning, and teaching activities and assessment. Key concepts that underpin EdVee are drawn from systems engineering and product development. We demonstrate its value to course design through two case studies: the design of a new course and the evaluation of an existing course. Click here to read the corresponding ISSOTL blog post.